POTENSI ANTIBAKTERI EKSTRAK KULIT MANGGIS (GARCINIA MANGOSTANA L.) TERHADAP STAPHYLOCOCCUS AUREUS - Suci Ayu Fitriani; Widaninggar Rahma Putri; Wiwit Probowati (Bajang Institute, 2026)
Infectious diseases remain a major cause of global morbidity and mortality. Staphylococcus aureus is an important pathogenic bacterium that can cause a wide range of infections, from mild skin infections to severe systemic diseases, and is increasingly associated with antibiotic resistance. Mangosteen peel (Garcinia mangostana L.) contains bioactive compounds with antibacterial activity. This study aimed to determine the antibacterial activity of mangosteen peel extract at concentrations of 50%, 75%, and 100% against Staphylococcus aureus in vitro. This study was a true experimental study with a completely randomized design. Antibacterial activity was assessed using the disc diffusion method on Mueller Hinton Agar (MHA). The inhibition zone diameter was measured after 24 h of incubation at 35–37°C. Data were analyzed using the Shapiro–Wilk test, followed by the Kruskal–Wallis test. The results showed that mangosteen peel extract inhibited the growth of Staphylococcus aureus, with mean inhibition zone diameters of 9.7 ± 1.64 mm (50%), 10.5 ± 1.51 mm (75%), and 11.4 ± 1.26 mm (100%), indicating moderate antibacterial activity. Although the inhibition zone tended to increase with increasing extract concentration, no statistically significant difference was observed among the tested concentrations (p > 0.05). Mangosteen peel extract exhibited potential antibacterial activity against Staphylococcus aureus.